Intellectual Polarization among Gayo Muslims Following the Dutch Ethical Policy: Polarisasi Intelektual Muslim Gayo Pasca Kebijakan Politik Etis Belanda - Sempena, Zikri Iwan (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2025)
Abstract The implementation of the Dutch Ethical Policy, particularly in the field of education, marked a turning point in the cultural development of the Indonesian archipelago. It fostered the rise of a new intellectual class driven by aspirations for reform and emancipation, who articulated their ideas through socio-religious and educational organizations. This study investigates the intellectual polarization among Gayo Muslims that emerged in the wake of this policy. It addresses two core inquiries: the causes behind the polarization and its subsequent dynamics. Adopting a historical method with a socio-cultural approach, the research finds that the Dutch educational system significantly influenced this intellectual divide. Initially resisted by traditionalist circles who perceived it as a deviation from Islamic orthodoxy the Western model of education gradually produced a cohort of critical thinkers. These individuals began to challenge established religious rituals, labeling them as inconsistent with the essence of Islam. As a result, Gayo Muslim intellectuals became ideologically fragmented into two primary camps: the traditionalist group (Kaom Tue) and the modernist or reformist group (Kaom Mude).